Vascular plant one‐zinc‐finger protein 1/2 transcription factors regulate abiotic and biotic stress responses in Arabidopsis. (12th February 2013) - Nakai, Yusuke; Nakahira, Yoichi; Sumida, Hiroki; Takebayashi, Kosuke; Nagasawa, Yumiko; Yamasaki, Kanako; Akiyama, Masako; Ohme‐Takagi, Masaru; Fujiwara, Sumire; Shiina, Takashi; Mitsuda, Nobutaka; Fukusaki, Eiichiro; et al.
Summary Plants adapt to abiotic and biotic stresses by activating abscisic acid‐mediated (ABA) abiotic stress‐responsive and salicylic acid‐(SA) or jasmonic acid‐mediated (JA) biotic stress‐responsive pathways, respectively. Although the abiotic stress‐responsive pathway interacts antagonistically with the biotic stress‐responsive pathways, the mechanisms that regulate these pathways remain largely unknown. In this study, we provide insight into the function of vascular plant one‐zinc‐finger proteins (VOZs) that modulate various stress responses in Arabidopsis. The expression of many stress‐responsive genes was changed in the voz1voz2 double mutant under normal growth conditions. Consistent with altered stress‐responsive gene expression, freezing‐ and drought‐stress tolerances were increased in the voz1voz2 double mutant. In contrast, resistance to a fungal pathogen, Colletotrichum higginsianum, and to a bacterial pathogen, Pseudomonas syringae, was severely impaired. Thus, impairing VOZ function simultaneously conferred increased abiotic tolerance and biotic stress susceptibility. In a chilling stress condition, both the VOZ1 and VOZ2 mRNA expression levels and the VOZ2 protein level gradually decreased. VOZ2 degradation during cold exposure was completely inhibited by the addition of the 26S proteasome inhibitor, MG132, a finding that suggested that VOZ2 degradation is dependent on the ubiquitin/26S proteasome system. In voz1voz2, ABA‐inducible transcription factor CBF4 expression was enhanced significantly even under normal growth conditions, despite an unchanged endogenous ABA content. A finding that suggested that VOZs negatively affect CBF4 expression in an ABA‐independent manner. These results suggest that VOZs function as both negative and positive regulators of the abiotic and biotic stress‐responsive pathways, and control Arabidopsis adaptation to various stress conditions.